Charismatic leadership in local politics: A study of the political articulation of power in Kalipare, Malang Regency - Khoiron Khoiron; Rico Tomboti (Universitas Merdeka Malang, 2025)
This article examines the practice of political articulation of power carried out by a Village Head during their leadership. The practice of articulating power is ethical but also political because the public understands that what is done is a sign of power politics that can be said to be